2007
DOI: 10.1007/s11010-007-9663-7
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid phenethyl ester induces mitochondria-mediated apoptosis in human myeloid leukemia U937 cells

Abstract: Caffeic acid phenyl ester (CAPE), a biologically active ingredient of propolis, has several interesting biological properties including antioxidant, anti-inflammatory, antiviral, immunostimulatory, anti-angiogenic, anti-invasive, anti-metastatic and carcinostatic activities. Recently, several groups have reported that CAPE is cytotoxic to tumor cells but not to normal cells. In this study, we investigated the mechanism of CAPE-induced apoptosis in human myeloid leukemia U937 cells. Treatment of U937 cells with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 26 publications
6
45
0
Order By: Relevance
“…Similar results were obtained by Jin et al [34], who performed a similar experiment on human leucoma cells line U937 and stated that CAPE has a citotoxic activity non-related to concentration and time exposure on cancer cells. Using the DAPI dye application, they observed the changes characteristic for apoptosis in cells nuclei.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were obtained by Jin et al [34], who performed a similar experiment on human leucoma cells line U937 and stated that CAPE has a citotoxic activity non-related to concentration and time exposure on cancer cells. Using the DAPI dye application, they observed the changes characteristic for apoptosis in cells nuclei.…”
Section: Discussionsupporting
confidence: 88%
“…HT-29 Hernandez et al [42] Caffeic acid phenethyl ester A549, LS 180, HeLa, NCTC clone L 929, M12.C3.F6 Chen et al [43] Caffeic acid phenethyl ester BxPC-3, PANC-1 Lee et al [44] Caffeic acid phenethyl ester SK-Hep1 Lee et al [45] Caffeic acid phenethyl ester HepG2 Lee et al [46] Caffeic acid phenethyl ester Daoy Jin et al [47] Caffeic acid phenethyl ester U937 Jung et al [48] Caffeic acid phenethyl ester MCF7, MDA 231 Lin et al [49] Caffeic acid phenethyl ester C6 expression levels was verified in cells from leukaemia patients treated with Manisa propolis, due to chrysin. [57] The cytotoxic effect of polyphenolic/flavonoid compounds on different leukaemia cell lines was evaluated using five different flavonoids (quercetin, caffeic acid, chrysin, naringenin and naringin) and five leukaemia cell lines (MOLT, JURKAT, HL-60, RAJI and U937).…”
Section: Sh-sy5ymentioning
confidence: 99%
“…Jin et al [17] investigated the mechanism of CAPE-induced apoptosis in U937 cells. They showed that CAPE decreased cell viability in dose-dependent and time dependent manner, DNA fragmentation and nuclear condensation in cancer cells and apoptotic action accompanied by release of cytochrome c, reduction of Bcl-2 expression, increase of Bax expression [17].…”
Section: Discussionmentioning
confidence: 99%